Factor Pricing and Income Distribution from an Islamic Perspective - Endah Sutriningsih (CV. ITTC INDONESIA, 2026)
This study examines factor pricing and income distribution from an Islamic economic perspective based on the principles of justice, balance, and social welfare. Islam allows prices to be determined through a fair market mechanism as long as they do not involve injustice, exploitation, monopoly, or hoarding. In certain circumstances, however, government intervention is permitted to maintain market stability and economic justice, as emphasized by Ibn Taymiyyah. Income distribution occupies a central role in Islamic economics to prevent wealth concentration and reduce social inequality. Distribution instruments such as zakat, infaq, sadaqah, waqf, and inheritance function as redistributive mechanisms to ensure the fulfillment of basic human needs. This research employs a qualitative approach using library research with descriptive-analytical methods. The findings indicate that Islamic concepts of pricing and income distribution aim to achieve social justice, economic balance, and sustainable welfare for society.